Determination of the affiliation of metastases in metachronous polyneoplasias of the breast and soft tissues of the thigh - T. N. Popova; V. Yu. Barsukov; A. S. Tolstokorov (Опухоли женской репродуктивной системы)
A clinical case of primary multiple metachronous malignant breast tumors and a rare malignant schwannoma of the right hip is presented. Difficulties in differential diagnosis arose with the appearance of a metastatic process in the lungs, solving the issue of their source and further treatment. In oncological practice, only morphological examination can finally verify the diagnosis. The choice of treatment regimen depends on the affiliation of metastases to a particular tumor. At the first immunohistochemical examination, tumor foci in the lung were regarded as breast cancer metastases, which it allowed to conduct 4 courses of polychemotherapy according to the TS scheme (paclitaxel + cyclophosphane) with negative dynamics. This led to doubt about the correctness of determining the source of the metastatic process. Repeated immunohistochemical examination revealed that the metastatic lesion of the lung tissue was a consequence of the progression of malignant schwannoma of the right hip. Appropriate polychemotherapy was prescribed.